PERANCANGAN CLOUD STORAGE MENGGUNAKAN OWNCLOUD DAN UBUNTU SERVER STUDI KASUS PADA PT. INDONESIA NIPPON SEIKI - Mochamad Yusuf Romdoni1; Irma Yunita Ruhiawati (Teknik Informatika Fakultas Ilmu Komputer, 2019)
Nowadays, almost all technology based on cloud computing knows that the trend language is Cloud computing, this technology has almost everyone in all corners of the earth feel it because indeed all applications used to use these technologies both on computers or on Android. In this good opportunity discussed how to build cloud computing by analyzing the approach to the user through question and answer to the user in everyday life then collecting data that can be used as material for designing Cloud computing systems accompanied by the results of related literature study. the cloud computing. Of the several stages of the analysis are used at the design stage using the Waterfall technique so that we can clearly see the flow of development of this system to the stage of its implementation, Cloud computing will always provide answers to all internet users how important the technology is in daily life that has been network based ssalah one example of the benefits we use is storage media or called Cloud Storage, on this occasion the object to be used as a development is PT. Nippon Seiki, whose data processing management is currently high enough that it must be accompanied by good data security, therefore it is necessary to build a cloud computing that privately for companies will be the right solution.